Environmental Health Risk Assessment of Air Pollutants in Online Motorcycle Taxi Drivers in the Special Capital Region of Jakarta - Meithyra Melviana Simatupang; Erna Veronika; Ahmad Irfandi; Rahmi Garmini (Universitas Airlangga, 2022)
Introduction: Online motorcycle taxi drivers spend most of their time outside as either driving or waiting for their customers. Therefore, chances of exposure to various air pollutants are higher and may cause various health problems, especially the respiratory problems. Methods: This is a descriptive study that used the Environmental Health Risk Analysis method to estimate the Risk Quotient (RQ) from exposure to PM10, SO2, CO, O3, and NO2 in drivers. The RQ was calculated based on exposure concentrations from the Special Capital Region of Jakarta Environment Agency; daily working hours, working days in a year, and working period obtained from interviews; additionally, body weight measurement, reference concentration (RfC), and the default value of inhalation intake were also collected. The population of this study was adult online motorcycle taxi drivers who operate around areas which become the air quality measurement stations in the Special Capital Region of Jakarta with a total sample of 81 people. Results and Discussion: The RQ for all minimum, average, and maximum concentrations of SO2, CO, and NO2 were <1. While for the average and maximum concentrations of PM10 and the maximum concentration of O3, the RQ was >1. The safe concentrations, work duration, and the number of working days also surpassed the maximum safety limit levels. Conclusion: PM10 and O3 ambient exposures are categorized unsafe for drivers. Environmental health efforts are necessary to reduce the concentration of air pollutants, and the guidelines to reduce pollutants exposure should be provided for drivers.